(untitled) (Reflection and Critique Law Magazine, 2024)
This article intends to analyze the recent proposal of social security reform, in contrast to the acquired rights emphasizing the important guiding principles of social security, as the example of the principle of the dignity of the human person, which aims at a dignified life for the citizen. The present study seeks to investigate the changes that social security reform brings to the law and its effects on society. To what extent has the “right” been restricted or not in the face of changes proposed by the current government with a focus on issues such as increasing age and time spent contributing. This requires a brief history of the origin of social security rights to the present day. Starting as it came to its concept and consolidation. We will also see through the guiding principles whether the changes now proposed by the pension reform, as far as their scope violates or not the current normative law. The research took place in a bibliographical referential methodological way, through books, articles and works that deal with the theme and the Brazilian legislation in force. Keywords: Pension; Retirement; Remodeling.